Analysis of the Impact of the Merdeka Curriculum Policy on Stakeholders at Primary School - Wardani, Helda Kusuma; Sujarwo, Sujarwo; Rakhmawati, Yeni; Cahyandaru, Pramudya (SCAD Independent, 2023)
The 2022 Merdeka curriculum for primary schools is a policy of the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia for implementation for the 2022–2023 school year. This policy analysis aimed to thoroughly criticize the policy aspects of the 2022 Merdeka primary school curriculum for obtaining a prescription for the future. The method of policy analysis in the form of narrative discussion was used to obtain adequate prescriptive results. The results obtained from this policy analysis showed that changes in the Merdeka curriculum in 2022 for primary schools would be incremental. Changing the curriculum followed the innovation process so that innovation attributes were met. The 2022 Merdeka curriculum for primary schools was to restore the regressed learning quality and prepare for the golden generation of 2045. The Character Education Strengthening Program and the Pancasila Student Profile Program demonstrate that ethics education is critical to the golden generation's success.